A massively parallel computer model of propagation through a two-dimensional cardiac syncytium. - Fishler MG; Thakor NV (Pacing & Clinical Electrophysiology, 1991)
A computer model of electrical propagation through a two-dimensional (2D) sheet of cardiac tissue has been developed to run on the massively parallel processor Connection Machine (CM-2) computer. The transmembrane ionic currents in each of 16,364 (128 x 128) 100 x 100 um² patches of cardiac tissue are described by modified Beeler-Reuter membrane equations. These equations, along with the parabolic differential equation derived from 2D cable theory, are solved in parallel to study normal and abnormal 2D propagation. The sheet is paced with planar waves at a basic cycle length of 500 msec (control). When a premature ectopic stimulus of sufficient strength and appropriate timing is then applied to a local region of the syncytium, one of two types of reentry is observed: (a) stable figure-of- eight reentry, or (b) unstable but self-sustaining 'fibrillation-like' reentry. During this fibrillatory activity, action potential durations are 79.8 ± 36.8 msec (control = 244.9 ± 0.9 msec) and coupling intervals average 96.7 ± 31.3 msec (control = 500 ± 0 msec). We also observed that passive electrotonically- induced depolarization of already refractory tissue extended the refractory period of that tissue, and that the duration of this extension depended on the magnitude of the electrotonic effect.